Human memory modeled with standard analog and digital circuits inspiration for man-made computers - Burger, John Robert 1940- (Wiley, 2009)
Gain a new perspective on how the brain works and inspires new avenues for design in computer science and engineering. This unique book is the first of its kind to introduce human memory and basic cognition in terms of physical circuits, beginning with the possibilities of ferroelectric behavior of neural membranes, moving to the logical properties of neural pulses recognized as solitons, and finally exploring the architecture of cognition itself. It encourages invention via the methodical study of brain theory, including electrically reversible neurons, neural networks, associative memory sys.
Includes bibliographical references (pages 359-360) and index. - Print version record
Keywords: Memory -- Computer simulation; Artificial intelligence; Neural networks (Computer science); Memory -- physiology; Neural Networks, Computer; Artificial Intelligence; Biometry -- methods; Computer Simulation; Models, Neurological; Intelligence artificielle; Réseaux neuronaux (Informatique); Simulation par ordinateur; artificial intelligence; simulation; SCIENCE; Cognitive Science; Memory; Computer simulation